Computational Design of Laser-Cut Bending-Active Structures. (October 2022) - Rodriguez, Emmanuel; Bonneau, Georges-Pierre; Hahmann, Stefanie; Skouras, Mélina
Abstract: We propose a method to automatically design bending-active structures, made of wood, whose silhouettes at equilibrium match desired target curves. Our approach is based on the use of a parametric pattern that is regularly laser-cut on the structure and that allows us to locally modulate the bending stiffness of the material. To make the problem tractable, we rely on a two-scale approach where we first compute the mapping between the average mechanical properties of periodically laser-cut samples of mdf wood, treated here as metamaterials, and the stiffness parameters of a reduced 2D model; then, given an input target shape, we automatically select the parameters of this reduced model that give us the desired silhouette profile. We validate our method both numerically and experimentally by fabricating a number of full scale structures of varied target shapes. Graphical abstract: Highlights: Parametric family of laser-cut metamaterials with tunable bending capabilities. Homogenization method for Bending properties of metamaterials. Two-scale algorithm for the inverse design of bending-active structures.